DOI: 10.1007/978-3-540-87875-9_26
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Conformance Relation for Incremental Development of Behavioural Models

Abstract: In this paper, we show how to implement the conformance relation on transition systems. The computability of this relation relies on the composition of two operators: the reduction relation whose computability has been proven in our previous work, and the merge function of acceptance graphs associated with transition systems under comparison. It is formally demonstrated, and illustrated through a case study whose analysis is performed by a JAVA prototype we have developed. This research work is developed in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
3
2
2

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The algorithm we have developed to check conformance is based on the notion of process merging. The theorem on which it is based can be found in Luong et al (2008). It has been implemented in a Java tool, called IDCM (Incremental Development of Conformant Models) which provides, as we will see in the following, other comparison relations.…”
Section: The Conformance Relationmentioning
confidence: 99%
“…The algorithm we have developed to check conformance is based on the notion of process merging. The theorem on which it is based can be found in Luong et al (2008). It has been implemented in a Java tool, called IDCM (Incremental Development of Conformant Models) which provides, as we will see in the following, other comparison relations.…”
Section: The Conformance Relationmentioning
confidence: 99%
“…To the best of our knowledge, no work has yet to formalise and implement the incremental development and verification of behavioural UML models. In previous works (Luong et al, 2008), we have shown how to implement a conformance relation between two UML state machines. Then, we have studied and implemented specific relations based on conformance and suitable for incremental development (Luong, 2010;Courbis et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the conformance relation has been defined by [17], we are still not aware of any published method to compute it. We have thus proposed an implantation of this relation and pointed out how extension and refinement relations can be defined from the conformance relation [18,19]. In the same way, we have implemented the procedure allowing to check if a component can substitute another one, whatever its environment may be [24].…”
Section: Liveness Analysismentioning
confidence: 99%